The New Hospitality Paradigm: Leveraging Absorptive Capacity for AI and 5G-Enabled Innovation - Irawan R.D Budianto; Supina Supina; Fajri Fajri; Hadita Hadita (Dinasti Publisher, 2024)
The hospitality industry is undergoing a significant transformation due to the integration of artificial intelligence (AI) and 5G technology. This new paradigm is characterized by innovative services and experiences that are made possible by these technological advancements. AI is being integrated into hospitality services, revolutionizing the industry, particularly by enhancing the efficiency and effectiveness of guest interactions and back-end operations. The advent of 5G technology is poised to usher in a new epoch for the hospitality industry, not just as a technological upgrade, but as a transformative force reshaping guest experiences and operational efficiencies. The integration of 5G technology in the hospitality industry can enhance the guest experience by providing personalized services and smart room controls. However, ensuring strong and uninterrupted mid-band coverage is a significant barrier to implementing 5G in hospitality. Successful AI applications in hospitality include personalized recommendations and chatbots that automate routine tasks. The absorptive capacity of the hospitality industry is critical for leveraging external knowledge for competitive advantage. Investing in research and development activities is essential for innovation and staying competitive in this rapidly evolving industry.